A study of libration points in CR3BP under albedo effect - Idrisi, M Javed (International Journal of Advanced Astronomy, 2016)
In this paper this is investigated how albedo perturbed the libration points from its original position? It is found that there exist five libration points, three collinear and two non-collinear and all the libration points are affected by Albedo. The non-collinear libration points are stable for a critical value of mass parameter µ ≤ µc, where µc = µo − (0.00891747 + 0.222579k)α (µo is the critical mass parameter for classical case) but collinear libration points are still unstable.